Book review: Anil K. Khandelwal, Transformational Leadership in Banking: Challenges of Governance, Leadership and HR in a Digital and Disruptive World. Issue 2 (April 2023) - Bhatnagar, Jyotsna
Anil K. Khandelwal, Transformational Leadership in Banking: Challenges of Governance, Leadership and HR in a Digital and Disruptive World, 2021, . New Delhi: Sage Publications, 514 pp., 45.00. ISBN: 9789353887568 (Hardback).